Pengembangan Media Belajar dengan Desain Khusus Bagi ABK Slow Learning - Opi Andriana; Aulia Miftahul Janna; Putri Wahyuni (Populer: Jurnal Penelitian Mahasiswa, 2024)
The aim of this research is to find out what media can improve the thinking abilities of slow learner ABK students. The method used in this research design is a literature review study. Literature study is a form of research used to collect data sources related to a topic found in the field. Data collection for literature studies was carried out using the Google Scholar search tool. The screening results matched the required data, there were 7 national journal articles based on the articles found and analyzed. The results of this research are the discovery of media that are suitable and can support the success of slow learner ABK students in improving their thinking abilities, namely bussy box media, stamp game media, and puzzles.